WOMEN RETAIL FARM INPUTS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
In the Gambian Women in Development project, the Agricultural Inputs Office acts as a wholesaler of fertilisers, pesticides and seeds. In a precursor FAO project, nearly all the retailers were men (individuals, or groups of farmers usually involved...